Bluey mum school (Great Britain: Penguin Random House UK, 2022)
Bluey: Mum School, published by Penguin Young Readers, is a charming picture book based on the popular episode from the Bluey TV series. In the story, Bluey decides to skip bath time and instead runs her own "Mum School," using balloons as pretend children while Mum (Chilli) plays along as the evaluator. As Bluey tries to teach and control her balloon pupils, one stubborn balloon named Greenie refuses to cooperate, leading to frustration. When Bluey observes how Dad (Bandit) gently manages Bingo$1 (Bs behavior, she learns a more thoughtful and creative approach to parenting. After adjusting her strategy, she begins to succeed$1 (Buntil Greenie is blown out the window, leaving Bluey feeling like she$1 (Bs failed. Mum reassures her that even real mums struggle sometimes and that it$1 (Bs okay to start again tomorrow. With colorful illustrations, playful humor, and a heartwarming message about empathy, patience, and learning through play, Mum School is a delightful read for young children and parents alike.s
Bluey: Mum School is a light-hearted and meaningful picture book that blends imaginative play with real-life parenting lessons in a way that$1 (Bs accessible for young children. Through Bluey$1 (Bs pretend game of running a school for mums, the story explores themes like patience, empathy, and learning from mistakes. It encourages children to understand that caring for others$1 (Bwhether you're a parent or a playtime teacher$1 (Bis not always easy, and it's okay to not get it right every time. The book captures the warmth, humor, and emotional depth that make the Bluey series beloved by families, making it both entertaining and valuable for shared reading.s
Keywords: Imaginative play; Parent-child relationships; Emotional learning